Polarization properties and a local structure of (GeSe₂)x(Sb2Se₃)₁-x glasses - Malesh, V.I.; Rubish, V.V.; Shpak, I.I.; Rubish, V.M.; Puha, P.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The results of investigating different parameters (of glasses in Ge-Sb-Se system have been given. The values of structural-sensitive molar IR polarization F have been calculated and its concentrational dependence has been constructed. The polarity of chemical bonds has been estimated. It has been shown that with increasing the content of Sb₂Se₃ in the composition of the glasses the polarity of Sb-Se bonds rises. Within the limits of free volume conception the formation energy (Eh) and the volume (Vh) of microcavities have been calculated. Eh and Vh are structural-sensitive parameters of glassy materials. It has been shown that the inflection is observed in concentrational dependences of investigated and calculated parameters of (GeSe₂)x(Sb₂Se₃)₁-x glasses in the vicinity of x = 0.60. It testifies to the structural changes in the glasses while changing the composition. The structure of (GeSe₂)x(Sb₂Se₃)₁-x glasses is mainly determined by structural units GeSe₄/₂ and SbSe₃/₂, to be statistically distributed into matrices. The increase of Sb₂Se₃ content in GeSe₂ is accompanied by a gradual transition from tetrahedrally co-ordinated structural units in glassy GeSe₂, to trigonally co-ordinated - in Sb₂Se₃.